Synthesis and Antimicrobial Activity of 1-(4’-Trifluoro methylphenyl)-2-phenyl-4-(benzylidene/substituted Benzylidene/2’-furylidene/2’-thienylidene)-imidazolin-5-ones - Solankee, Anjani; Kapadia, Kishor; Thakor, Indrajit; Patel, Jayesh; Lad, Smruti (Asian Journal of Chemistry, 2016)
Some new 1-(4'-trifluoromethyl phenyl)-2-phenyl-4-(benzylidene/substituted benzylidene/2'-furylidene/2'-thienylidene)-imidazolin-5-ones have been prepared by refluxing the mixture of 5-oxazolones with 4-amino benzotrifluoride in pyridine. The synthesized compounds were screened for their antibacterial activity. Structures of the synthesized compounds have been elucidated on the basis of their elemental analysis and spectral data.